Leaf epicuticular waxes of eleven Euphorbia species (Euphorbiaceae) from the central Balkans: impact on chemotaxonomy - Krstić, Gordana; Aljančić, Ivana; Stanković, Jovana; Cvetković, Mirjana; Marin, Petar; Janaćković, Peđa; Tešević, Vele (Archives of Biological Sciences, 2019)
The presence of n-alkanes, free alcohols and free acids in leaf epicuticular wax extracts of 22 samples of 11 Euphorbia L. species belonging to the sections Paralias, Esula, Myrsiniteae and Helioscopia, 10 of which were never examined before, were analyzed by gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS), and n-alkane C27 was detected as the principal component of leaf epicuticular waxes in the majority of the examined species, while the most abundant free alcohol was C26. Three Euphorbia species belonging to section Helioscopia were characterized by a predominance of alcohol C28. Free acid (C16) was the major component in 21 investigated samples. The usefulness of n-alkanes and free alcohols and free acids as potential chemotaxonomic markers is briefly discussed. https://doi.org/10.2298/ABS180608041K Received: June 8, 2018; Revised: August 31, 2018; Accepted: September 12, 2018; Published online: September 21, 2018 How to cite this article: Krstić G, Aljančić I, Stanković J, Cvetković M, Marin P, Janaćković P, Tešević V. Leaf epicuticular waxes of eleven Euphorbia species (Euphorbiaceae) from the Central Balkans: Impact on chemotaxonomy. Arch Biol Sci. 2019;71(1):21-6.